Decreased microbial co-occurrence network stability and SCFA receptor level correlates with obesity in African-origin women. Issue 1 (December 2018) - Dugas, Lara; Bernabé, Beatriz; Priyadarshini, Medha; Fei, Na; Park, Seo; Brown, Laquita; Plange-Rhule, Jacob; Nelson, David; Toh, Evelyn; Gao, Xiang; Dong, Qunfeng; Sun, Jun; et al.
Abstract We compared the gut microbial populations in 100 women, from rural Ghana and urban US [50% lean (BMI < 25 kg/m2 ) and 50% obese (BMI ≥ 30 kg/m2 )] to examine the ecological co-occurrence network topology of the gut microbiota as well as the relationship of short chain fatty acids (SCFAs) with obesity. Ghanaians consumed significantly more dietary fiber, had greater microbial alpha-diversity, different beta-diversity, and had a greater concentration of total fecal SCFAs (p-value < 0.002). Lean Ghanaians had significantly greater network density, connectivity and stability than either obese Ghanaians, or lean and obese US participants (false discovery rate (FDR) corrected p-value ≤ 0.01).Bacteroides uniformis was significantly more abundant in lean women, irrespective of country (FDR corrected p < 0.001), while lean Ghanaians had a significantly greater proportion ofRuminococcus callidus, Prevotella copri, andEscherichia coli, and smaller proportions of Lachnospiraceae, Bacteroides andParabacteroides . Lean Ghanaians had a significantly greater abundance of predicted microbial genes that catalyzed the production of butyric acid via the fermentation of pyruvate or branched amino-acids, while obese Ghanaians and US women (irrespective of BMI) had a significantly greater abundance of predicted microbial genes that encoded for enzymes associated with the fermentation of amino-acids such as alanine, aspartate, lysine and glutamate. Similar to lean Ghanaian women, mice humanized with stool from the lean Ghanaian participant had a significantly lower abundance of family Lachnospiraceae and genusBacteroides andParabacteroides, and were resistant to obesity following 6- weeks of high fat feeding (p-value < 0.01). Obesity-resistant mice also showed increased intestinal transcriptional expression of the free fatty acid (Ffa ) receptorFfa2, in spite of similar fecal SCFAs concentrations. We demonstrate that the association between obesity resistance and increased predicted ecological connectivity and stability of the lean Ghanaian microbiota, as well as increased local SCFA receptor level, provides evidence of the importance of robust gut ecologic network in obesity.